TLC profiling and antioxidant activity of phenolic compound from Sterculia oblongata bark extract - MURNINGSIH, TRI; PRAPTIWI, PRAPTIWI; LIANA, LIANA; FATHONI, AHMAD (Nusantara Bioscience, 2019)
Abstract. Murningsih T, Praptiwi, Liana, Fathoni A. 2019. TLC profiling and antioxidant activity of phenolic compound from Sterculia oblongata bark extract. Nusantara Bioscience 11: 44-48. In the present study, we investigated the total phenolic content and in- vitro antioxidant activity of Sterculia oblongata. Total phenolic content (TPC) of the methanol extract was examined by Folin-Ciocalteu reagent and gallic acid as standard. The in-vitro antioxidant activity was performed by DPPH free radical scavenging activity and ?-carotene bleaching assay. The result showed that the TPC of methanol extract was the highest (P